Enabling Conditions for Consumer-Centric Business Models in the United Kingdom Energy Market - Hardy, Jeffrey; Mazur, Christoph (Frontiers in Energy Research, 2020)
To achieve ambitious UK decarbonisation targets, consumers will need to engage with energy services more so than they have done to date. This engagement could be active or delegated, where in the latter consumers pass responsibility for engagement to a third party in return for ceding some control over decisions. To date, insight into the barriers to consumer adoption of future business models has been limited. To address this gap this study explored benefits, risks and enabling conditions using two extreme consumer-centric business models, 3rd Party Control and Shared Economy, using elements of a backcasting approach. The approach yielded information from stakeholders on what would have to be true for one of the business models to dominate the market. The results show substantial agreement across the expert groups on five key issues that will need to be addressed in the near-term to enable energy business model innovation in the UK market. These are: (1) Space to enable business model innovation is crucial; (2) Smart devices and data must be interoperable and secure; (3) Energy businesses need to improve service standards; (4) Solutions are required for consumers in all situations; and (5) Targeted carbon regulation is required.